The Russia-Ukraine War: Causes, Consequences and Solutions - Dana Mohammed Danish Aladdin Sajadi (Eurasian Journal of Management & Social Sciences, 2024)
The Russia-Ukraine War stands out as a significant conflict in modern times, profoundly affecting both regional and global stability. An ongoing war has been taking place between Russia and Ukraine since 2014 because of the Ukrainian revolution with the annexation of Crimea by Russia. On February 24th, 2022, when President Putin declared the special military operation marked the beginning of a full-fledged war in Ukraine. Geopolitically speaking this war has resulted in a significant shift as Russia faces greater isolation and scrutiny from the global community while Ukraine seeks stronger ties with Western powers. Besides that, the conflict has resulted in countless deaths along with millions having been displaced which in turn led to an ongoing humanitarian crisis. The world before and after the military operation will not be the same; several actors are involved in flaming and escalating the situation, which led to one of the worst disasters of the twenty-first century. In this study, the author adopted a qualitative research approach, delving into the intricate causes of the conflict through thematic analysis of a wide range of secondary sources. The research closely examines historical, geopolitical, and ethnic tensions that have played a significant role in escalating hostilities. The central focus of this research is to untangle the intricate web of interests and power dynamics that are influencing the conflict. Hence, the conflict impacts both regional and global geopolitics, affecting the stability of the international system. It highlights the absence and failure of diplomacy in preventing the conflict from escalating.